Effect of Foliar Application of Boron and Seed Scarification on Some Vegetative Growth and Yield of Broad Bean Vicia Faba L. Local Var. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
A field experiment was conducted for the 2017/2018 agricultural season in the area of ​​Yusufiya (20 km south of Baghdad governorate) to study the effect of boron  spraying and seed pretreatment before planting on growth and yield of Vicia Faba var faba. The study included two factors representing 4 levels of boron (0 , 25 , 50 , and 75 mg.L-1), three methods of seeds pretreatment  before planting (seeds without treatment, soaking the seeds for 24 hours with water, soaking the seeds with water for 12 hours and scratching their cover) , RCBD  where used with three replicates , the results show:                                                                                         There were significant differences between levels of boron spray and seed pretreatment method and their interaction on the positive effect on growth parameters and yield studied. The high levels of boron spraying led to early flowering , maturity and significant increase in plant height, number of branches, number of leaves, leaf area, chlorophyll content  percentage of dry matter, total number of  pods  per plant, the number of seeds per pod, weight of 100 seeds and the yield of plant compared to the treatment without spraying, the treatment of  boron spray  (75 mgm. L-1 ) gave low values to 50% flowering  90.8 days, maturity first pod of 98.5 days, while gave the highest average to growth and yield above was 72.67 cm, 6.10 branch, 84.97 leaf , 1006.03 cm2, 44.03 spad ,  30.54% , 22.40 pod per plant , 4.75 seed per pod , 198.55 gm ,  and 220.54 gm respectively, while the pretreatment of soaking the seeds with water before planting for 12 hours and scratching their cover gave the lowest period to 50% flowering  91.68 days and 101.88 days  to pod maturity and  highest average was 74.60 cm, 6.08 branches, 94.53 leaf,1093.67 cm2 ,  44.43 spad , 29.30%,  20.26 pod.plant-1 , 4.88 seeds.pod-1 ,  205.56 g , and 214.39 g respectively. While the interaction treatment  (spray boron 75 mg.L-1  + seed soaking with water to 12 hours) gave  less period to flowering and pod  maturity and highest values to above growth and yield parameters.